Organisational routines – the interplay of legal standards and professional discretion. (July 2016) - Ottesen, Eli; Møller, Jorunn
Discretion is described as a hallmark of professional work. Professional discretion rests on trust in the ability of certain occupational groups to make sound decisions 'on behalf' of societal authorities. It has been suggested that in Europe, managerialist-influenced policies with increased focus on control and accountability have placed pressure on professional discretion. Although earlier studies have demonstrated tensions between external and internal accountability, they have not highlighted how legal forms of authority are key aspects in the regulation of education, or how professionals handle legal standards in their practices. The purpose of this study is to understand the interplay between legal standards and professional discretion. An organisational-routines perspective is used to examine this interplay. Empirically, the students' legal rights to a good psychosocial environment are used as a case. Based on interviews with principals, deputies and teachers in Norwegian schools, the paper examines how legal norms are translated into social practices, and how practitioners construct and legitimise their work. The study shows how preventive and remedial measures are prevalent in Norwegian schools. When laws and regulations require specific procedures, they are transformed into routines based on the schools' iterative practices. The study adds an empirical analysis to current understandings of juridification in education.